2012
DOI: 10.1016/j.seizure.2012.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Novel Myoclonin1/EFHC1 mutations in Mexican patients with juvenile myoclonic epilepsy

Abstract: The frequency of Myoclonin1/EFHC1 mutations in our sample is 7.3%. Thus, we conclude that mutations in the Myoclonin1/EFHC1 gene are an important cause of JME in Mexican patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…26 We included medical records that had the following variables: VPA dose, blood levels, and length of time taking VPA; if any of these variables were missing, records were excluded. The last taken dose of VPA was recorded, and the patient must have been on that dose for at least one year of monitoring.…”
Section: Methodsmentioning
confidence: 99%
“…26 We included medical records that had the following variables: VPA dose, blood levels, and length of time taking VPA; if any of these variables were missing, records were excluded. The last taken dose of VPA was recorded, and the patient must have been on that dose for at least one year of monitoring.…”
Section: Methodsmentioning
confidence: 99%
“…However, mutations in another epilepsy gene (EF-hand domain containing protein 1) have been found in multiple GGE kindreds and, importantly, the penetrance of EFHC1 mutations is less than 100%. We quantified the number of affected and unaffected male and female GGE patients who possessed disruptive EFHC1 mutations that were identified in four different familial studies (Annesi et al, 2007; Jara-Prado et al, 2012; Suzuki et al, 2004, Medina et al, 2008). We found that of the patients that possessed EFHC1 mutations, 24/42 females (57%) and 15/36 males (42%) expressed a GGE syndrome whereas the remainder lacked a discernable phenotype, or simply exhibited childhood febrile seizures, or an asymptomatic abnormal EEG.…”
Section: Human Syndromes With Absence Seizures: Sex Differences?mentioning
confidence: 99%
“…14), were not available in 2004 when variants of the EF-hand domain (C-terminal) containing 1 gene (EFHC1) were reported as disease-causing mutations in myoclonic and grand mal clonic-tonic-clonic (CTC) convulsions produced by juvenile myoclonic epilepsy (JME). Consequently, all EFHC1 variants discovered in the first decade of this millennium and reported with respect to epilepsy or not [15][16][17][18][19][20][21][22][23][24][25][26][27][28] have not been "vetted" through NHGRI and ACMG guidelines. More importantly, both NHGRI and ACMG guidelines advise that "with evidence on variants evolving" and the "content of sequencing tests expanding, " "rigorous evaluation" and "reanalysis of variants are encouraged" to prevent misannotation of the pathogenicity of variants in public databases.…”
mentioning
confidence: 99%